26th International Conference on Optical Fiber Sensors 2018
DOI: 10.1364/ofs.2018.the68
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive vibration sensor based on an asymmetric multi-core optical fiber

Abstract: We report on a simple, highly sensitive interferometric vibration sensor that operates in reflection mode, which is suitable to monitor low frequencies with low amplitudes. The sensor was fabricated with a short segment of three strongly coupled core optical fiber. The device was protected with capillary tubes and it was placed in cantilever position. The sensor exploits the ultrahigh sensitivity of supermodes to small bending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In addition to the periodicity of vibration, the amplitude of vibration, which indicates the magnitude of the restoring force, can also be used for acceleration measurement [ 20 ]. It has been widely reported that high-sensitivity vibration measurement can be achieved by using MCF interferometer-based sensors [ 16 , 17 , 20 , 43 , 45 , 70 , 71 , 113 , 114 , 116 , 117 ] because these sensors are sensitive to curvature changes, which will contribute to the high sensitivity of the vibration sensors. Table 2 summarizes various MCF interferometer-based vibration sensors.…”
Section: Discussion and Comparisonmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the periodicity of vibration, the amplitude of vibration, which indicates the magnitude of the restoring force, can also be used for acceleration measurement [ 20 ]. It has been widely reported that high-sensitivity vibration measurement can be achieved by using MCF interferometer-based sensors [ 16 , 17 , 20 , 43 , 45 , 70 , 71 , 113 , 114 , 116 , 117 ] because these sensors are sensitive to curvature changes, which will contribute to the high sensitivity of the vibration sensors. Table 2 summarizes various MCF interferometer-based vibration sensors.…”
Section: Discussion and Comparisonmentioning
confidence: 99%
“…It indicates that an MCF-based interferometric vibration sensor can provide a large frequency-measurement range, varying from 1 mHz [ 20 ] to 12 kHz [ 17 ]. These compact and high-sensitivity sensors can be used in many fields, such as the long-term monitoring of construction and mechanical structures [ 71 ], contactless vital signs monitoring [ 43 ], seismic measurement [ 116 ], accelerometers [ 20 ], etc.…”
Section: Discussion and Comparisonmentioning
confidence: 99%
See 3 more Smart Citations